The coastal environmental profile of Brunei Darussalam resource assessment and management issues - Thia-Eng, Chua; Ming, Chou Loke; Sadorra, Marie Sol M. (Makati City ICLARM, 1987)
ICLARM Technical Reports; 18
Keywords: Environmental policy; Coastal zone management; Renewable natural resources